Fast1h-nmr species differentiation method for camellia seed oils applied to spanish ornamentals plants. Comparison with traditional gas chromatography - Barreiro, Rocío; Rodríguez-Solana, Raquel; Alonso, Leocadio; Salinero, Carmen; López-Sánchez, José Ignacio; Peréz-Santín, Efren (MDPI, 2022)
Camellia genus (Theaceae) is comprised of world famous ornamental flowering plants. C. japonica L. and C. sasanqua Thunb are the most cultivated species due to their good adaptation. The commercial interest in this plant linked to its seed oil increased in the last few years due to its health attributes, which significantly depend on different aspects such as species and environmental conditions. Therefore, it is essential to develop fast and reliable methods to distinguish between different varieties and ensure the quality of Camellia seed oils. The present work explores the study of Camellia seed oils by species and location. Two standardized gas chromatography methods were applied and compared with that of data obtained from proton nuclear magnetic resonance spectroscopy (1H-NMR) for fatty acids profiling. The principal component analysis indicated that the proposed1H-NMR methodology can be quickly and reliably applied to separate specific Camellia species, which could be extended to other species in future works.
Keywords: authentication; camellia oil; chemometrics; chromatographic techniques; nuclear magnetic resonance; quality; Scopus; JCR